Revitalisasi Nilai-Nilai Akhlak Mulia dalam Perspektif Al-Islam dan Kemuhammadiyahan - Andi Arbaina Fariza; Bahaking Rama; Sudarni Sudarni; Fatima Azzahra (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to increase understanding and relationships related to the revitalization of noble moral values ​​in the Al-Islam Kemuhammadiyahan perspective. This research was prepared using a qualitative approach using the literature review method. Research data was collected using reference sources from several research articles and books using document triangulation. It is hoped that this research can contribute to organizations involved in helping to realize the Islamic character of the nation's next generation through education. The results of this research provide an overview and understanding of the urgency of religious integrity in building Islamic character based on noble moral values ​​in building the next generation of civilized nation. Apart from that, the implications of this research can be a guide to the formation of Islamic character and ethics, strengthening noble moral values, and can be a guide in the field of education, especially universities with Islamic nuances in designing programs that support the progressive process of revitalizing noble moral values. and maximum.